Supplementation of Turmeric Flour on Survival of Asian Redtail Catfish (Hemibagrus Nemurus) - Desi Rahmadani Siagian; Benny Heltonika (Jurnal Natur Indonesia, 2023)
Asian redtail catfish culture activities are still constrained by the low survival rate in the seeds phase, one of the causes is cannibalism behavior. Several attempts have been made to improve the survival of these fish, and several studies have shown that turmeric powder can increase survival in several species. Based on this, this study aimed to evaluate the addition of turmeric flour with the coating method on the survival rate of Asian redtail catfish (Hemibagrus nemurus) seeds. This study used a completely randomized design using four treatments and was repeated three times. The treatment used was the supplemented turmeric flour to commercial feed which had a protein of 40%., the treatments were 0.0 g kg-1 (K), 2.5 g kg-1 (TK2.5), 5.0 g kg-1 (TK5.0), and 7.5 g kg-1 feed (TK7.5). The size of the Asian redtail catfish was 2.09±0.17 cm, with a stocking density of 3 L-1, and reared in an aquarium measuring 38x25x22 cm3. The study was conducted for 30 days and fed at satiation four times a day. The parameters measured were survival, cannibalism (cannibal type, cannibal index, normal death), and growth performance (absolute weight, absolute length, specific weight growth, and specific length growth). The results showed that TK5.0 was able to increase the survival rate and decrease the cannibalism index and normal death rate. Furthermore, the supplemented turmeric flour did not have an impact on the absolute weight, absolute length, specific growth rate, and specific length